Coordination of transcriptional and translational regulations in human epithelial cells infected by Listeria monocytogenes. Issue 10 (2nd October 2020) - Besic, Vinko; Habibolahi, Fatemeh; Noël, Benoît; Rupp, Sebastian; Genovesio, Auguste; Lebreton, Alice
ABSTRACT: The invasion of mammalian cells by intracellular bacterial pathogens reshuffles their gene expression and functions; however, we lack dynamic insight into the distinct control levels that shape the host response. Here, we have addressed the respective contribution of transcriptional and translational regulations during a time-course of infection of human intestinal epithelial cells by an epidemic strain of Listeria monocytogenes, using transcriptome analysis paralleled with ribosome profiling. Upregulations were dominated by early transcriptional activation of pro-inflammatory genes, whereas translation inhibition appeared as the major driver of downregulations. Instead of a widespread but transient shutoff, translation inhibition affected specifically and durably transcripts encoding components of the translation machinery harbouring a 5ʹ-terminal oligopyrimidine motif. Pre-silencing the most repressed target gene ( PABPC1 ) slowed down the intracellular multiplication of Listeria monocytogenes, suggesting that the infected host cell can benefit from the repression of genes involved in protein synthesis and thereby better control infection.